Pendapatan Usahatani Padi Hibrida dan Padi Inbrida di Kabupaten Bogor, Propinsi Jawa Barat (Farm Income of Hybrid Rice and Inbred Rice in Bogor Regency, West Java Province) - Qhoirunisa, Astri Sabrina; Nurmalina, Rita (JURNAL PANGAN, 2013)
Beras adalah komoditas pangan pokok masyarakat Indonesia. Kebutuhan yang tinggi terhadap beras menjadi dasar penting bagi Indonesia untuk meningkatkan produksi dan produktivitas padi nasional melalui program ekstensifikasi maupun intensifikasi pertanian. Peningkatan produktivitas melalui intensifikasi pertanian salah satunya diwujudkan melalui penanaman padi hibrida. Penelitian ini bertujuan mendeskripsikan keragaan usahatani, menganalisis pendapatan usahatani, termasuk imbangan penerimaan dan biaya (R/C rasio) usahatani padi hibrida dan padi inbrida di Kabupaten Bogor. Hasil penelitian menunjukkan pendapatan atas biaya tunai per hektar per musim pada usahatani padi hibrida sebesar Rp 8.265.583,- sedangkan pada usahatani padi inbrida sebesar Rp 8.875.299,-. Pendapatan atas biaya total per hektar per musim pada usahatani padi inbrida sebesar Rp 2.660.588,- sedangkan pada usahatani padi hibrida pendapatan atas biaya total bernilai negatif yang berarti petani padi hibrida mengalami kerugian sebesar Rp 235.003,-. Nilai R/C rasio atas biaya tunai pada usahatani padi hibrida sebesar 2,15 sedangkan pada usahatani padi inbrida sebesar 2,40. Nilai R/C rasio atas biaya total pada usahatani padi hibrida sebesar 0,99, sementara pada usahatani padi inbrida senilai 1,21.Rice is a staple food in Indonesia. Increasing demand for rice becomes an important base for rice farming in Indonesia to increase national rice production and productivity through extensification and intensification of agricultural programs. One way to increase productivity through intensification program is planting hybrid rice. The purposes of this study are to describe the variability of rice farming activities and to analyze farm income, including the ratio between revenue and cost of hybrid and inbred rice farming in Bogor regency. The results show that the income generated based on cash costs per hectare per season on hybrid rice farming is Rp 8,265,583 while for the inbred rice farming is Rp 8,875,299. Income generated based on total costs per hectare per season for inbred rice farming is Rp 2,660,588 while for the hybrid rice farming is negative; meaning that hybrid rice farmers suffer a loss of Rp 235,003. Value of R/C ratio based on cash cost on hybrid rice farming equals to 2.15, while for the inbred rice farming is 2.40. The value of R/C ratio based on total cost of the hybrid rice farming equals to 0.99, while for the inbred rice farming is 1.21.